PERANCANGAN SISTEM INFORMASI PEMESANAN NOMOR ANTRIAN PADA BAUK STKIP PGRI SUMATERA BARAT - Mary, Thomson; Irsyadunas, Irsyadunas; Pratama, Andika Befni (Jurnal EDik Informatika, 2020)
Queuing Manual System at the STKIP PGRI West Sumatera General and Financial Administration Board (BAUK) needs to be upprove  for employees to facilitate employees in carrying out service. The design of information system is carried out by the SDLC (System Development Life Cycle) method which consists of planning, analysis, design an implementation. The analytical aid used is the Unified Modeling Language (UML) in the form of Use Case Diagram., Activity Diagrams, Class Diagrams, and Sequence Diagram. Data in this design is the number of queues, types of services. The design of this information system uses testing using Black Box Testing which will be tasted for each module using data that has been prepared. The final result is an application information system than helping BAUK STKIP PGRI West Sumatera in managing queue and improving student serevice and convenience in administrasi.